2023
DOI: 10.1186/s40337-023-00853-5
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of research literature on eating and body image for transgender and nonbinary youth

Katie Heiden-Rootes,
Whitney Linsenmeyer,
Samantha Levine
et al.

Abstract: Background Transgender and nonbinary (TGNB) adolescents and young adults are underrepresented in the literature on eating disorders and body image-related problems, despite increased mental health disparities and emerging research showing high associations between gender dysphoria, body image, and eating disorders among TGNB youth. Aims The scoping review was designed to critically examine the research on TGNB adolescents and young adults who exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…First, studies were separated by age to create youth (children to young adult where young adults were analyzed as unique developmental stage) and adult (adult-only samples, 18 years old and older with broad age ranges and analyzed together as an all-adult sample) tables for separate analysis. Again, this manuscript will only report on the adult samples and the youth and young adult articles are summarized in a separate scoping review manuscript (Heiden-Rootes et al [24]).…”
Section: Review Procedures and Analysismentioning
confidence: 99%
“…First, studies were separated by age to create youth (children to young adult where young adults were analyzed as unique developmental stage) and adult (adult-only samples, 18 years old and older with broad age ranges and analyzed together as an all-adult sample) tables for separate analysis. Again, this manuscript will only report on the adult samples and the youth and young adult articles are summarized in a separate scoping review manuscript (Heiden-Rootes et al [24]).…”
Section: Review Procedures and Analysismentioning
confidence: 99%
“…For example, Participant Eight was denied the privilege of spirituality support while in treatment due to their identity as a Moroccan Jew despite evidence that suggests spiritual health to be integral and powerful in the success of some patients' ED recovery [44]. Research has found that Transgender and gender non-binary populations experience EDs and ED recovery in unique ways; changes to body size and shape facilitate gender dysphoria and increase the complexity of recovery, yet gender was excluded from treatment entirely, creating challenges for Participants Eight and Eleven [45]. Participant Ten, who experienced housing instability while in treatment, felt unsupported due to the stigma that suggests housing instability cannot coexist maintaining recovery [46].…”
Section: Discussionmentioning
confidence: 99%